2009
DOI: 10.1007/s10533-009-9388-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertical change in dissolved organic carbon and oxygen at the water table region of an aquifer recharged with stormwater: biological uptake or mixing?

Abstract: Decreases in dissolved organic carbon (DOC) and dissolved oxygen (DO) with increasing depth below the groundwater table are often considered as evidence for aerobic respiration; however, they may reflect mixing of infiltrating water and groundwater. We found that groundwater DOC concentration was on average 0.3 mg C l -1 higher and DO concentration 1.5 mg O 2 l -1 lower at recharge sites replenished with stormwater than at reference sites fed by direct infiltration of rain water from the land surface. Groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…5). Surface-derived recharge then mixes and dilutes with ambient groundwater (Foulquier et al 2010) leading to an initial DOC concentration. DOC is then removed from the aquifer/compartment by the combined effects of biodegradation and sorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Surface-derived recharge then mixes and dilutes with ambient groundwater (Foulquier et al 2010) leading to an initial DOC concentration. DOC is then removed from the aquifer/compartment by the combined effects of biodegradation and sorption.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other groundwater environments have also reported an inverse relationship between DOC concentrations and the thickness of the unsaturated zone (Pabich et al 2001;Chapelle et al 2013), and DOC concentration decreases along discrete groundwater flowpaths (Findlay and Sobczak 1996;Baker et al 2000). The decrease in DOC concentrations has been attributed to a combination of biodegradation (Findlay and Sobczak 1996;Baker et al 2000;Rauch and Drewes 2005;Grünheid et al 2005), sorption onto aquifer materials (Neff and Asner 2001;Kalbitz et al 2003), and dilution (Foulquier et al 2010).…”
Section: Doc Concentrations and Uv Absorbance In Groundwatermentioning
confidence: 96%
“…Other alteration processes must be active as surface DOM infiltrates into the groundwater. Hydrologic mixing can influence DOC concentrations in groundwater (Foulquier et al 2010), but mixing does not appear to be the major factor controlling the composition of DOM in groundwater. Sorption alters the composition of DOM by preferentially removing hydrophobic macromolecules, but it has less influence on bioavailable components (e.g., amino acids and carbohydrates) (Jardine et al 1989;Kaiser et al 2004;Inamdar et al 2012).…”
Section: Dom Bioavailability In Groundwatermentioning
confidence: 99%
“…On the sink side, the physical accessibility of solid-phase geogenic TEA, predominantly Fe(III), and Mn(IV) species, is dependent on their crystallinity, which is not commonly analyzed except for sites of research interest (Villatoro-Monzón et al, 2003;Lovley et al, 2004;Scherr et al, 2016). Reduced species may be recharged in the upper aquifer portions, as molecular oxygen infiltrated by rain (Foulquier et al, 2010) or on a discontinuous scale from upgradient regions, such as nitrate from agricultural use. Source dissolution processes are characterized to a better extent for electron acceptor DNAPLs, such as single-component halogenated hydrocarbons (Klenk and Grathwohl, 2002;Guilbeault et al, 2005;Johnston et al, 2014).…”
Section: Introductionmentioning
confidence: 99%